Thermal / environmental barrier coating with high heat insulation, thermal shock resistance and CMAS corrosion resistance as well as preparation method and application of thermal / environmental barrier coating
Preparation of Si-HfO2/Yb2Si2O7/Yb2SiO5/(Dy0.2Ho0.2Er0.2Tm0.2L on the surface of SiC/SiC ceramic matrix composite material of aero-engine hot end parts u0.2)2Hf2O7 thermal/environmental barrier coating solves the problems of water oxygen corrosion and CMAS molten salt corrosion in high-temperature gas environments, achieves high thermal insulation, thermal shock resistance and CMAS corrosion resistance, and extends the service life of the coating life.
Patent Information
- Application Number
- CN202411269844.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2025-01-24
AI Technical Summary
The silicon carbide ceramic composite material of the hot end components of the existing aircraft engine is easily corroded by water and oxygen and CMAS molten salt in a high-temperature gas environment, resulting in structural strength decline, and traditional coatings are prone to cracks and peeling during thermal cycles.
Plasma spraying-physical gas deposition technology is prepared for Si-HFO2/YB2SI2O7/YB2SIO5/(DY0.2HO0.2er0.2lu0.2) 2HF2O7 heat/ambient disorder coating system on SIC/SIC ceramic base composite material surface. The design and material selection of layers to improve the coating's thermal insulation, heat shock and anti -CMAS corrosion performance.
It achieves high thermal insulation, thermal shock resistance and CMAS corrosion resistance in a high temperature environment of 1500°C, extending the service life of the coating and ensuring the stable service of CMC composite materials.
Smart Images

Figure CN119351941A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of aviation engine environmental barrier coatings, and specifically relates to a high heat insulation, thermal shock resistance, and CMAS corrosion resistance thermal / environmental barrier coating, and a preparation method and application thereof. Background Art
[0002] As aircraft engines pursue higher thrust-to-weight ratios, the surface temperature of hot end components is expected to exceed 1500°C. Even with the use of thermal barrier coatings and film cooling, nickel-based high-temperature alloys are difficult to meet these extreme conditions. f / SiC, CMC) has become the preferred material for hot end components of aircraft engines due to its excellent specific strength and high-temperature mechanical properties, and can replace traditional high-temperature alloy components to achieve structural weight reduction and improve fuel efficiency.
[0003] However, in the presence of steam or corrosive substances, CMC is continuously degraded, forcing the structural strength of the components to gradually decline. Therefore, the protection of environmental barrier coatings (EBCs) has become a necessary condition for the long service life of CMC components. Western developed countries started research on EBCs early and proposed the third generation of rare earth silicate environmental barrier coating system, based on Si / Yb 2 Si 2 O 7 / Yb 2 SiO 5 For example, Yb has become the first choice for the research and development and application of environmental barrier coatings at home and abroad because of its good phase stability and excellent water vapor corrosion resistance and low volatility in high-speed gas environments. 2 Si 2 O 7 The coefficient of thermal expansion (CTE) of Yb is close to that of CMC, but its resistance to water and oxygen corrosion is not outstanding, so it is suitable as an intermediate layer; 2 SiO 5 It has better resistance to water and oxygen corrosion, but its CTE is larger, so it is suitable as a surface layer.
[0004] However, in the above system, the thermally grown oxide (TGO) of the pure Si bonding layer will repeatedly undergo cristobalite phase transition during thermal cycling, accompanied by CTE mutation and volume expansion, resulting in excessive thermal stress accumulation inside the coating, causing cracking and peeling, which limits the development of the system. 2The introduction of Si bonding layer can improve the high temperature performance and creep performance of the bonding layer while providing good bonding strength, inhibit the formation of thermally grown oxide (TGO) in the bonding layer at high temperature, and reduce the tendency of the coating to crack during service. In addition, due to the presence of alkaline molten salt slag corrosive media (CaO-MgO-Al 2 O 3 -SiO 2 , CMAS), and Yb 2 SiO 5 The anti-CMAS corrosion performance is still insufficient. Therefore, in order to further improve the anti-CMAS performance and thermal insulation performance of EBC, a layer of (Dy 0.2 Ho 0.2 Er 0.2 Tm 0.2 Lu 0.2 ) 2 Hf 2 O 7 Thermal barrier coating (TBC) forms a T / EBC multilayer coating. However, the more layers the coating has, the more likely it is that the coating will fail during thermal cycling due to mechanical instability of the interface caused by thermal expansion mismatch between layers, which will easily cause cracks. Therefore, there are problems such as weak thermal shock resistance, which limits the service life. Previous studies have found that (Dy 0.2 Ho 0.2 Er 0.2 Tm 0.2 Lu 0.2 ) 2 Hf 2 O 7 Compared with other TBC candidate ceramic materials, ceramic materials also have the advantage of lower CTE and closer to CMC matrix. Therefore, the T / EBC system not only has excellent thermal insulation and CMAS resistance, but also good thermal shock resistance and longer thermal cycle service life, which is conducive to improving the service temperature and service life of ceramic matrix composite components in the complex environment of the hot end of aircraft engines.
[0005] At present, the most widely used method for preparing EBC or TBC is atmospheric plasma spraying (APS) technology. Although APS technology has low cost, the coating produced by it has large porosity and large thermal residual stress, which is prone to produce a large number of stress cracks during service, causing the coating to peel off and reduce its service life. The coating produced by the plasma spray-physical vapor deposition (PS-PVD) process has high density and uniformity. Through process adjustment, gas, liquid, and solid multiphase deposition of spray powder can be achieved. The deposition efficiency is high and non-line-of-sight deposition can be achieved, which has great advantages in the preparation of T / EBC coatings for CMC composite turbine blades. Summary of the invention
[0006] The purpose of the present invention is to overcome and supplement the deficiencies in the prior art, and to provide a high heat insulation, thermal shock resistance, and CMAS corrosion resistance thermal / environmental barrier coating and its preparation method and application. The present invention uses plasma spraying-physical vapor deposition technology to prepare Si-HfO on the surface of SiC / SiC ceramic matrix composite materials. 2 / Yb 2 Si 2 O 7 / Yb 2 SiO 5 / (Dy 0.2 Ho 0.2 Er 0.2 Tm 0.2 Lu 0.2 ) 2 Hf 2 O 7 Thermal / environmental barrier coating system to protect SiC f / SiC composite materials serve stably as hot-end components of aircraft engines and are protected from water-oxygen corrosion and CMAS molten salt erosion in harsh high-temperature gas environments. They are a highly potential environmental barrier coating with good application prospects.
[0007] In order to solve the problems of the prior art, the technical solution adopted by the present invention is:
[0008] A high heat insulation, thermal shock resistance, and CMAS corrosion resistance thermal / environmental barrier coating, the thermal / environmental barrier coating comprises SiC f / SiC matrix, Si-HfO 2 Adhesive layer, Yb 2 Si 2 O 7 Middle layer, Yb 2 SiO 5 The middle layer and (Dy 0.2 Ho 0.2 Er 0.2 Tm 0.2 Lu 0.2 ) 2 Hf 2 O 7 The top layer has a distinct interface between the layers and is tightly bonded. 2 The bonding layer is composed of Si and HfO 2 It is prepared according to a molar ratio of 85:15; the interior of the thermal / environmental barrier coating is a classic lamellar structure with high density and no obvious through cracks and holes.
[0009] Preferably, the Si-HfO 2 The average thickness of the bonding layer is 58 μm, Yb2 Si 2 O 7 The average thickness of the middle layer is 63 μm, Yb 2 SiO 5 The average thickness of the middle layer is 77 μm. 0.2 Ho 0.2 Er 0.2 Tm 0.2 Lu 0.2 ) 2 Hf 2 O 7 The average thickness of the top layer was 81 μm.
[0010] The method for preparing the above-mentioned high thermal insulation, thermal shock resistance and CMAS corrosion resistance thermal / environmental barrier coating comprises the following steps:
[0011] Step S1, take Si and HfO 2 Powder drying, weighing Si and HfO according to the molar ratio of 85:15 2 After the powder is formed, it is added into a ball mill for wet ball milling to obtain a first mixed slurry, and then dried to obtain a first powder;
[0012] Step S2, respectively take Yb 2 O 3 Powder and SiO 2 Powder drying, weighing Yb according to the molar ratio of 1:2 2 O 3 and SiO 2 After the powder is formed, the mixture is added into a ball mill for wet ball milling to obtain a second mixed slurry, and after the second mixed slurry is dried, it is added into a high-temperature furnace for solid phase reaction, and finally crushed and sieved in sequence to obtain a second powder;
[0013] Step S3, respectively take Yb 2 O 3 and SiO 2 Powder drying, weighing Yb according to the molar ratio of 1:1 2 O 3 and SiO 2 After the powder is formed, the mixture is added into a ball mill for wet ball milling to obtain a third mixed slurry, and after the third mixed slurry is dried, it is added into a high-temperature furnace for solid phase reaction, and finally crushed and sieved in sequence to obtain a third powder;
[0014] Step S4, respectively take Dy 2 O 3 、Ho 2 O 3 , Er 2 O 3 、Tm 2 O 3、Lu 2 O 3 and HfO 2 The powder was dried and Dy was weighed according to the molar ratio of 0.2:0.2:0.2:0.2:0.2:2 2 O 3 、Ho 2 O 3 , Er 2 O 3 、Tm 2 O 3 、Lu 2 O 3 and HfO 2 The powder is added into a ball mill for wet ball milling to obtain a fourth mixed slurry, and the fourth mixed slurry is dried and then added into a high-temperature furnace for solid phase reaction, and finally crushed and sieved in sequence to obtain a fourth powder;
[0015] Step S5, adding adhesive and solvent to the first powder, the second powder, the third powder and the fourth powder to prepare slurry with a solid content of 40-55%, and spray granulating them to obtain Si-HfO 2 Powder, Yb 2 Si 2 O 7 Powder, Yb 2 SiO 5 Powder and (Dy 0.2 Ho 0.2 Er 0.2 Tm 0.2 Lu 0.2 ) 2 Hf 2 O 7 Powder;
[0016] Step S6, preparing SiC f / SiC substrate, sandblasting the substrate surface to an average roughness Ra of 5-8 μm, then ultrasonically cleaning and drying the substrate, and fixing the substrate on a spraying fixture;
[0017] Step S7, evacuate the plasma spray-physical vapor deposition chamber, then preheat the substrate. When the substrate is preheated to the set temperature, switch to the spraying program and control the powder feeder to sequentially deliver Si-HfO 2 Powder, Yb 2 Si 2 O 7 Powder, Yb 2 SiO 5 Powder, (Dy 0.2 Ho 0.2 Er 0.2 Tm 0.2 Lu0.2 ) 2 Hf 2 O 7 Powder, and spray the bonding layer Si-HfO on the substrate in sequence through a spray gun 2 , Yb 2 Si 2 O 7 Middle layer, Yb 2 SiO 5 The middle layer and (Dy 0.2 Ho 0.2 Er 0.2 Tm 0.2 Lu 0.2 ) 2 Hf 2 O 7 Top layer, cooled to obtain Si-HfO 2 / Yb 2 Si 2 O 7 / Yb 2 SiO 5 / (Dy 0.2 Ho 0.2 Er 0.2 Tm 0.2 Lu 0.2 ) 2 Hf 2 O 7 Thermal / Environmental Barrier Coatings.
[0018] Preferably, the powder drying temperature in step S1, step S2, step S3 and step S4 is 100-120°C, and the drying time is 1-3h; the wet ball milling steps are as follows: Si and HfO 2 Powder, Yb 2 O 3 Powder and SiO 2 Powder, Dy 2 O 3 、Ho 2 O 3 , Er 2 O 3 、Tm 2 O 3 、Lu 2 O 3 and HfO 2The powder, anhydrous ethanol as a solvent and ball milling beads are added to a ball mill for wet ball milling, wherein the mass ratio of the added powder, anhydrous ethanol and ball milling beads is 1:0.8:1; the rotation speed of the wet ball mill is 450-550rpm, the mixing time is 10-16h, the drying temperature of the first mixed slurry, the second mixed slurry, the third mixed slurry and the fourth mixed slurry is 80-100°C, and the drying time is 12-14h.
[0019] Preferably, the temperature of the solid phase reaction in step S2, step S3 and step S4 is 1400-1550°C, the solid phase reaction time is 4-8h, and the median particle size of the second powder, the third powder and the fourth powder is 30-50μm.
[0020] Preferably, in step S5, the amount of adhesive added is 4-8%, the inlet temperature is 200-300° C., the outlet temperature is 90-130° C., the frequency of the atomizing disk is 20-50 Hz, and the feed pump speed is 30-50 rpm.
[0021] Preferably, in step S6, the sandblasting pressure is 0.3-0.4 MPa, the sandblasting angle is 50-60°, the sandblasting distance is 120-150 mm, the sandblasting time is 1-3 min, and the solvents for ultrasonic cleaning are kerosene, acetone, and alcohol, respectively.
[0022] Preferably, the vacuuming of the cabin in step S7 is specifically as follows: the cabin pressure is pumped down to 0.5 mbar, then Ar is backfilled to 40 mbar, after Ar backfilling is completed, the spray gun is ignited, and the vacuum system is turned on again to pump the cabin pressure down to 1.5 mbar; the bonding layer Si-HfO is sprayed 2 The current is 1650A, the flow rate of argon is 110 liters / minute, the flow rate of hydrogen is 6 liters / minute, the powder feeding rate is 8g / min, the spray distance is 400mm, the preheating temperature is 500℃, and the pressure is 40mbar; spraying Yb 2 Si 2 O 7 The current of the middle layer is 2600A, the flow rate of argon is 100 liters / minute, the flow rate of helium is 20 liters / minute, the powder feeding rate is 20g / min, the spray distance is 1000mm, the preheating temperature is 900℃, and the pressure is 1.5mbar; spraying Yb 2 SiO 5 The current of the middle layer is 2600A, the flow rate of argon is 100 liters / minute, the flow rate of helium is 20 liters / minute, the powder feeding rate is 20g / min, the spray distance is 1000mm, the preheating temperature is 900℃, and the pressure is 1.5mbar; spraying (Dy 0.2 Ho 0.2 Er 0.2 Tm 0.2 Lu 0.2 )2 Hf 2 O 7 The current of the top layer is 2600A, the flow rate of argon is 35 liters / minute, the flow rate of helium is 60 liters / minute, the powder feeding rate is 20g / min, the spray distance is 1000mm, the preheating temperature is 1000℃, and the pressure is 1.5mbar.
[0023] Application of any of the above-mentioned thermal / environmental barrier coatings with high thermal insulation, thermal shock resistance and CMAS corrosion resistance in the preparation of protective coatings for aircraft engines.
[0024] The present invention prepares Si-HfO by spray granulation technology 2 , Yb 2 Si 2 O 7 Yb 2 SiO 5 and (Dy 0.2 Ho 0.2 Er 0.2 Tm 0.2 Lu 0.2 ) 2 Hf 2 O 7 Agglomerated powder has high sphericity, good fluidity, suitable particle size and uniform composition; Si-HfO 2 The bonding layer provides good bonding strength and excellent high temperature performance. 2 Si 2 O 7 The intermediate layer alleviates the mismatch of thermal expansion coefficients between the coating and the substrate, reducing cracking and peeling of the coating. 2 SiO 5 The middle layer has excellent resistance to water and oxygen corrosion. 0.2 Ho 0.2 Er 0.2 Tm 0.2 Lu 0.2 ) 2 Hf 2 O 7 The top layer has the advantages of low thermal conductivity, excellent anti-CMAS performance and low CTE, which makes the T / EBC coating have a high service temperature and a long service life. It can protect the CMC composite material from water-oxygen corrosion and CMAS corrosion in harsh high-temperature gas environments, allowing it to serve stably as a hot end component of an aircraft engine.
[0025] Beneficial effects:
[0026] Compared with the prior art, the present invention provides a high heat insulation, thermal shock resistance, and CMAS corrosion resistance thermal / environmental barrier coating and its preparation method and application.
[0027] It has the following advantages:
[0028] (1) The present invention uses spray granulation technology to prepare raw material powders for thermal / environmental barrier coatings, which have high sphericity, good fluidity, and excellent thermal stability, and can better meet the requirements of subsequent spraying technology.
[0029] (2) The present invention adopts plasma spraying-physical vapor deposition technology on SiC f Si-HfO prepared on the surface of SiC composites 2 / Yb 2 Si 2 O 7 / Yb 2 SiO 5 / (Dy 0.2 Ho 0.2 Er 0.2 Tm 0.2 Lu 0.2 ) 2 Hf 2 O 7 Thermal / environmental barrier coating has high density and uniformity. Through process adjustment, gas, liquid and solid multiphase deposition of spray powder can be achieved. The deposition efficiency is high and non-line-of-sight deposition can be achieved. It has great advantages in preparing EBC coatings on the surface of CMC composite turbine hot end components, thereby increasing the service temperature and extending the service life; and it has good mechanical bonding with the substrate and can withstand thermal shock performance assessment and CMAS resistance performance assessment at 1500°C; compared with traditional atmospheric plasma spraying technology, plasma spray-physical vapor deposition has the characteristics of high power and low vacuum, and the powder particles have a high flight speed (>300m / s). The prepared coating has low porosity and high density, which can effectively hinder the erosion and diffusion of corrosive media such as oxygen, and can ensure the stable service of CMC as the hot end component of aircraft engines and protect it from water and oxygen corrosion in harsh high-temperature gas environments.
[0030] (3) The present invention introduces rare earth oxide HfO on the basis of pure Si bonding layer 2 , can provide good bonding force while improving the high temperature performance and creep performance of the bonding layer, inhibit the formation of thermally grown oxide (TGO) in the bonding layer at high temperature, reduce the tendency of the coating to crack during service, and increase the service life of the coating, that is, improve the temperature bearing capacity and service life of the bonding layer, weaken the layer cracking and peeling phenomenon caused by the phase change of thermally grown oxide (TGO) in the bonding layer at high temperature, and is suitable as a bonding layer; Yb 2 Si 2 O 7 The CTE is close to that of CMC and Yb 2 SiO 5It has excellent water and oxygen corrosion resistance and is suitable for the middle layer of double EBC; the top layer material is selected (Dy 0.2 Ho 0.2 Er 0.2 Tm 0.2 Lu 0.2 ) 2 Hf 2 O 7 , low thermal conductivity, not only excellent thermal insulation and CMAS corrosion resistance, and low CTE mismatch with the CMC matrix. As the top TBC, it can improve the overall thermal insulation, thermal shock resistance and CMAS corrosion resistance of the T / EBC, that is, increase the coating service temperature and extend the thermal cycle service life. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 The morphology of the original powder obtained in Example 1 after spray granulation; (a) Si-HfO 2 ; (b) Yb 2 Si 2 O 7 ; (c) Yb 2 SiO 5 ; (d)(Dy 0.2 Ho 0.2 Er 0.2 Tm 0.2 Lu 0.2 ) 2 Hf 2 O 7 .
[0032] Figure 2 This is the surface morphology of the coating sample obtained in Example 1.
[0033] Figure 3 This is the cross-sectional morphology of the coating sample obtained in Example 1.
[0034] Figure 4 This is the surface morphology of the coating sample obtained in Example 1 after 100 cycles of thermal shock test at 1500°C.
[0035] Figure 5 This is the cross-sectional morphology of the coating sample obtained in Example 1 after 100 cycles of thermal shock test at 1500°C.
[0036] Figure 6 This is the cross-sectional morphology of the coating sample obtained in Example 1 after resisting CMAS corrosion at 1500°C for 50 hours. DETAILED DESCRIPTION
[0037] The present invention will be further described below in conjunction with specific drawings and embodiments.
[0038] Example 1
[0039] A thermal / environmental barrier coating with high thermal insulation, thermal shock resistance and CMAS corrosion resistance, comprising SiC f / SiC matrix layer, Si-HfO 2 Adhesive layer, Yb 2 Si 2 O 7 Middle layer, Yb 2 SiO 5 The middle layer and (Dy 0.2 Ho 0.2 Er 0.2 Tm 0.2 Lu 0.2 ) 2 Hf 2 O 7 The top layer, the Si-HfO 2 The bonding layer includes Si and HfO in a molar ratio of 85:15. 2 ;Si-HfO 2 The average thickness of the bonding layer is 58 μm, Yb 2 Si 2 O 7 The average thickness of the layer is 63 μm, and the Yb 2 SiO 5 The average thickness of the layer is 77 μm and (Dy 0.2 Ho 0.2 Er 0.2 Tm 0.2 Lu 0.2 ) 2 Hf 2 O 7 The average thickness of the layer was 81 μm.
[0040] The method for preparing the above-mentioned high thermal insulation, thermal shock resistance and CMAS corrosion resistance thermal / environmental barrier coating comprises the following steps:
[0041] Step S1, take Si and HfO 2 The powders were dried at 120 °C for 2 h, and then Si and HfO were weighed according to a molar ratio of 85:15. 2 The powder is added into a ball mill for wet ball milling to obtain a first mixed slurry, wherein the mass ratio of the powder, anhydrous ethanol and ball milling beads is 1:0.8:1; the speed of the wet ball milling is 500 rpm, the mixing time is 14 hours, and then the first mixed slurry is dried to obtain a first powder, the drying temperature of the first mixed slurry is 80° C., and the drying time is 14 hours;
[0042] Step S2, respectively take Yb2O 3 Powder and SiO 2The powder was dried at 120 °C for 2 h, and then Yb 2 O 3 and SiO 2 The powder is added into a ball mill for wet ball milling to obtain a second mixed slurry, wherein the mass ratio of the powder, anhydrous ethanol and ball milling beads is 1:0.8:1; the speed of the wet ball mill is 450 rpm, and the mixing time is 10 hours. The second mixed slurry is then dried at a drying temperature of 80°C for 12 hours, and then added into a high-temperature furnace for solid phase reaction at a solid phase reaction temperature of 1500°C for 4 hours. Finally, the synthesized powder is crushed and sieved to obtain a second powder, and the median particle size of the second powder is 30-50 μm.
[0043] Step S3, respectively take Yb 2 O 3 and SiO 2 The powder was dried at 120 °C for 2 h, and then Yb 2 O 3 and SiO 2 The powder is added into a ball mill for wet ball milling to obtain a third mixed slurry, wherein the mass ratio of the powder, anhydrous ethanol and ball milling beads is 1:0.8:1; the speed of the wet ball mill is 500 rpm, and the mixing time is 10 hours. The third mixed slurry is then dried at a drying temperature of 80°C for 12 hours, and then added into a high-temperature furnace for solid phase reaction at a solid phase reaction temperature of 1500°C for 4 hours. Finally, the synthesized powder is crushed and sieved to obtain a third powder, and the median particle size of the third powder is 30-50 μm.
[0044] Step S4, respectively take Dy 2 O 3 、Ho 2 O 3 , Er 2 O 3 、Tm 2 O 3 、Lu 2 O 3 and HfO 2 The powder was dried and then weighed according to the molar ratio of 0.2:0.2:0.2:0.2:0.2:2. 2 O 3 、Ho 2 O 3 , Er 2 O 3 、Tm 2 O 3 、Lu2 O 3 and HfO 2 powder, and add it to a ball mill for wet ball milling to obtain a fourth mixed slurry, the mass ratio of the powder, anhydrous ethanol and ball milling beads is 1:0.8:1; the speed of the wet ball mill is 550rpm, the mixing time is 16h, and then the third mixed slurry is dried, the drying temperature of the third mixed slurry is 80°C, the drying time is 12h, and it is added to a high-temperature furnace for solid phase reaction, the solid phase reaction temperature is 1550°C, and the solid phase reaction time is 8h, and finally the synthesized powder is crushed and sieved to obtain a fourth powder, and the median particle size of the fourth powder is 30-50μm;
[0045] Step S5, adding adhesive (the adhesive is purchased from Wuhan Meiqilin New Materials Co., Ltd. MQ-35 series) and solvent (distilled water) to the first powder, the second powder, the third powder and the fourth powder to prepare a slurry with a solid content of 40-55%, and spray granulating them to obtain Si-HfO 2 Powder, Yb 2 Si 2 O 7 Powder and Yb 2 SiO 5 Powder, adhesive content 4-8%, inlet temperature 200-300℃, outlet temperature 90-130℃, atomizing disk frequency 20-50Hz, feed pump speed 30-50rpm;
[0046] Step S6, prepare a 15mm×15mm×3mm SiC / SiC substrate, use a SiC abrasive with a diameter of 250μm to sandblast the substrate surface until the average roughness Ra is 5μm, the sandblasting pressure is 0.3MPa, the sandblasting angle is 50°, the sandblasting distance is 120mm, and the sandblasting time is about 1min. Then, the substrate is ultrasonically cleaned with kerosene, acetone, and alcohol in sequence, and the substrate is fixed on a spraying fixture after drying;
[0047] Step S7, write the manipulator heating and spraying program, input the process parameters in the spraying control system, close the cabin door after the preparation work is completed, start the vacuum system to pump the cabin pressure to 0.5mbar, and then backfill Ar to 40mbar. After Ar backfilling is completed, start the spray gun ignition, turn on the vacuum system again to pump the cabin pressure to 1.5mbar, the plasma jet gradually begins to expand as the cabin pressure decreases, and after the plasma jet is stable, control the spray gun to move according to the set program, start preheating the substrate, and switch to the spraying program. The equipment uses an O3CP type spray gun. During the spraying process, the tooling rotates at 60r / min. After the powder feeding program is started, the powder feeder is automatically turned on. After the powder feeding is stable, the powder feeder is controlled to sequentially transport Si-HfO 2 Powder, Yb2 Si 2 O 7 Powder, Yb 2 SiO 5 Powder and (Dy 0.2 Ho 0.2 Er 0.2 Tm 0.2 Lu 0.2 ) 2 Hf 2 O 7 The powder is then sprayed on the substrate with a bonding layer of Si-HfO 2 , Yb 2 Si 2 O 7 Middle layer, Yb 2 SiO 5 The middle layer and (Dy 0.2 Ho 0.2 Er 0.2 Tm 0.2 Lu 0.2 ) 2 Hf 2 O 7 The top layer is cooled to obtain the semi-finished product. The substrate temperature is monitored by an infrared thermometer, and the spray distance is adjusted by a manipulator. 2 SiO 5 During the coating process, the vacuum tank is properly supplemented with oxygen to prevent the crystal from losing oxygen. After the sample is cooled to room temperature in the vacuum environment at the end of spraying, air is introduced, the vacuum chamber is opened and the sample is taken out to obtain Si-HfO 2 / Yb 2 Si 2 O 7 / Yb 2 SiO 5 / (Dy 0.2 Ho 0.2 Er 0.2 Tm 0.2 Lu 0.2 ) 2 Hf 2 O 7 Thermal / environmental barrier coatings;
[0048] Among them, the spray bonding layer Si-HfO 2 The current is 1650A, the flow rate of argon is 110 liters / minute, the flow rate of hydrogen is 6 liters / minute, the powder feeding rate is 8g / min, the spray distance is 400mm, the preheating temperature is 500℃, and the pressure is 40mbar; spraying Yb 2 Si 2 O 7The current of the middle layer is 2600A, the flow rate of argon is 100 liters / minute, the flow rate of helium is 20 liters / minute, the powder feeding rate is 20g / min, the spray distance is 1000mm, the preheating temperature is 900℃, and the pressure is 1.5mbar; spraying Yb 2 SiO 5 The current of the middle layer is 2600A, the flow rate of argon is 100 liters / minute, the flow rate of helium is 20 liters / minute, the powder feeding rate is 20g / min, the spray distance is 1000mm, the preheating temperature is 900℃, and the pressure is 1.5mbar; spraying (Dy 0.2 Ho 0.2 Er 0.2 Tm 0.2 Lu 0.2 ) 2 Hf 2 O 7 The current of the top layer is 2600A, the flow rate of argon is 35 liters / minute, the flow rate of helium is 60 liters / minute, the powder feeding rate is 20g / min, the spray distance is 1000mm, the preheating temperature is 1000℃, and the pressure is 1.5mbar.
[0049] Example 2
[0050] For the Si-HfO of Example 1 2 / Yb 2 Si 2 O 7 / Yb 2 SiO 5 / (Dy 0.2 Ho 0.2 Er 0.2 Tm 0.2 Lu 0.2 ) 2 Hf 2 O 7 Thermal / Environmental Barrier Coatings Performance Tested
[0051] (I) Microscopic morphology observation
[0052] The spherical powder obtained in step S5 of Example 1 was pre-treated by magnetron sputtering and then placed in a scanning electron microscope for morphology observation. 2 / Yb 2 Si 2 O 7 / Yb 2 SiO 5 / (Dy 0.2 Ho 0.2 Er 0.2 Tm 0.2 Lu 0.2 ) 2 Hf2 O 7 The thermal / environmental barrier coating samples were mounted, then ground and polished, and placed in a scanning electron microscope. The surface morphology of the coating was observed using the secondary electron imaging mode, and the cross-sectional morphology of the coating was observed using the backscattering imaging model.
[0053] Figure 1 This is the morphology of different powders after spray granulation in Example 1. It can be seen from the figure that the first powder, the second powder, the third powder and the fourth powder all have distinct particles, regular shapes, and a high degree of spheroidization, which can better meet the requirements of the plasma spraying-physical vapor deposition process.
[0054] The flowability test of the above four powders found that the flow time of 50g of powder was less than 100 seconds, which further illustrates that the raw material powder for preparing thermal / environmental barrier coatings by spray granulation technology has good flowability.
[0055] Figure 2 The Si-HfO prepared in Example 1 2 / Yb 2 Si 2 O 7 / Yb 2 SiO 5 / (Dy 0.2 Ho 0.2 Er 0.2 Tm 0.2 Lu 0.2 ) 2 Hf 2 O 7 From the secondary electron image of the coating surface, it can be seen that its surface is composed of flat particles with good fusibility, the coating has a high density, and there are no obvious cracks and pores.
[0056] Figure 3 The Si-HfO prepared in Example 1 2 / Yb 2 Si 2 O 7 / Yb 2 SiO 5 / (Dy 0.2 Ho 0.2 Er 0.2 Tm 0.2 Lu 0.2 ) 2 Hf 2 O 7 Backscattered image of the coating cross section, where Si-HfO 2 Adhesive layer, Yb 2 Si 2 O 7 Middle layer, Yb 2SiO 5 The middle layer and (Dy 0.2 Ho 0.2 Er 0.2 Tm 0.2 Lu 0.2 ) 2 Hf 2 O 7 The average thickness of the top layer is 58μm, 63μm, 77μm and 81μm respectively. The inside of the coating is a classic lamellar structure with high density and no obvious through cracks and holes. There is a clear interface between the top layer, the double middle layer and the bonding layer, and the bonding layer is tightly bonded. The interface between the bonding layer and the substrate is obvious, showing good mechanical bonding.
[0057] (II) Thermal shock resistance test
[0058] The prepared coating sample was placed in a high temperature thermal shock furnace at 1500°C, kept warm for 1 hour, then taken out and cooled by a cold air blower, which was a thermal shock cycle. After 100 cycles, the cross section of the sample after thermal shock was observed by the backscattering mode of a scanning electron microscope.
[0059] Figure 4 The surface microstructure of the sample in Example 1 after thermal shock test. It can be seen that the surface of the thermal / environmental barrier coating is dense, but a small number of cracks also appear. This is due to the top (Dy 0.2 Ho 0.2 Er 0.2 Tm 0.2 Lu 0.2 ) 2 Hf 2 O 7 Although the CTE of the layer is low, there is still a certain gap between it and the CMC matrix. Therefore, after 100 times of thermal shock at 1500℃, the accumulated thermal stress of the coating will force (Dy 0.2 Ho 0.2 Er 0.2 Tm 0.2 Lu 0.2 ) 2 Hf 2 O 7 The top layer is cracked to relieve thermal stress.
[0060] Figure 5 The cross-sectional microstructure of the sample in Example 1 after thermal shock test. After 100 cycles of thermal shock of the thermal / environmental barrier coating, the substrate has no cracks, maintains good mechanical stability, and the bonding layer is still well bonded to the substrate. There is no obvious peeling phenomenon between the interfaces of the layers. In addition, Si-HfO 2 Light grey HfSiO is formed in the bonding layer 4 Phase and dark gray SiO 2The quartz phase has no obvious cracks, which proves that adding HfO to the Si bonding layer 2 Can weaken SiO 2 Quartz phase transition. Although, the top (Dy 0.2 Ho 0.2 Er 0.2 Tm 0.2 Lu 0.2 ) 2 Hf 2 O 7 Layer and Yb 2 SiO 5 The middle layer produces vertical cracks due to the thermal stress accumulated during the thermal shock process, but due to the Yb 2 Si 2 O 7 Possessing plastic deformation capability, vertical cracks can be formed in Yb 2 Si 2 O 7 / Yb 2 SiO 5 The bifurcation at the interface relieves the thermal stress accumulated in the coating during the thermal shock process, prolongs the crack expansion path, and prevents the bottom bonding layer and CMC matrix from being eroded by external corrosive media, proving that the T / EBC coating in this patent has good thermal shock resistance.
[0061] (III) Anti-CMAS performance test
[0062] First, according to 33CaO-9MgO-13AlO 1.5 -45SiO 2 The CMAS powder sample was prepared in a molar ratio of 1:1. The specific preparation method is referred to the literature: Hui Zhao, et al. Resistance of (Dy 0.2 Ho 0.2 Er 0.2 Tm 0.2 Lu 0.2 ) 2 Hf 2 O 7 top-coat material in thermal / environmental barrier coatings to calcium-magnesia-alumina-silicon attack at 1300℃and1500℃, Ceramics International, 50(2024)16572-16586.
[0063] https: / / doi.org / 10.1016 / j.ceramint.2024.02.148.
[0064] CMAS powder was dispersed in anhydrous ethanol under the action of a magnetic stirrer at a concentration of 30 mg / cm 2 The surface of the coating sample prepared above was coated with a ratio of and corroded at 1500℃ for 50h.
[0065] Figure 6 The cross-sectional micromorphology of the coating sample after CMAS corrosion for 50 hours. First, it can be seen that although a large amount of (Dy 0.2 Ho 0.2 Er 0.2 Tm 0.2 Lu 0.2 ) 2 Hf 2 O 7 The top layer is corroded by CMAS to form a reaction layer, and the residual (Dy 0.2 Ho 0.2 Er 0.2 Tm 0.2 Lu 0.2 ) 2 Hf 2 O 7 The layers peel off and vertical cracks appear. However, except for the Yb 2 SiO 5 In addition to a few vertical cracks extending in the middle layer, Yb 2 Si 2 O 7 Intermediate layer and Si-HfO 2 The bonding layer still maintains structural integrity, with no signs of peeling, cracking, or CMAS penetration. In addition, the interfaces between the layers and between the bonding layer and the substrate still maintain good bonding, ensuring that the CMC substrate is not corroded or structurally damaged.
[0066] The thermal shock test temperature and CMAS corrosion temperature of the coating prepared in Example 1 of the present invention are both 1500° C., which is higher than the ambient temperature in most tests in the art. Therefore, the coating of the present invention also has a “high thermal insulation” effect.
[0067] In summary, the Si-HfO obtained by plasma spraying-physical vapor deposition technology in the present invention 2 / Yb 2 Si 2 O 7 / Yb 2 SiO 5 / (Dy 0.2 Ho 0.2 Er0.2 Tm 0.2 Lu 0.2 ) 2 Hf 2 O 7 Excellent thermal / environmental barrier coating for SiC f The / SiC composite material matrix plays an effective protective role and is an aero-engine environmental barrier coating with great application potential.
[0068] The above specific implementation methods are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to examples, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should be included in the scope of the claims of the present invention.
Claims
1. A thermal / environmental barrier coating with high thermal insulation, thermal shock resistance and CMAS corrosion resistance, characterized by: The thermal / environmental barrier coating includes SiC f / SiC substrate, Si-HfO2 bonding layer, Yb2Si2O7 intermediate layer, Yb2SiO5 intermediate layer and (Dy 0.2 Ho 0.2 Er 0.2 Tm 0.2 Lu 0.2 )2Hf2O7 top layer, and there are obvious interfaces between the layers and they are tightly combined. The Si-HfO2 bonding layer is prepared from Si and HfO2 according to a molar ratio of 85:15; the interior of the thermal / environmental barrier coating is a classic lamellar structure with high density and no obvious through cracks and holes.
2. The high heat insulation, thermal shock resistance and CMAS corrosion resistance thermal / environmental barrier coating according to claim 1, characterized in that: The average thickness of the Si-HfO2 bonding layer is 58 μm, the average thickness of the Yb2Si2O7 intermediate layer is 63 μm, and the average thickness of the Yb2SiO5 intermediate layer is 77 μm. 0.2 Ho 0.2 Er 0.2 Tm 0.2 Lu 0.2 )The average thickness of the top layer of 2Hf2O7 is 81μm.
3. A method for preparing a thermal / environmental barrier coating having high thermal insulation, thermal shock resistance and CMAS corrosion resistance according to any one of claims 1 to 2, characterized in that: The following steps are involved: Step S1, respectively taking Si and HfO2 powders and drying them, weighing Si and HfO2 powders according to a molar ratio of 85:15, adding them into a ball mill for wet ball milling to obtain a first mixed slurry, and then drying to obtain a first powder; Step S2, respectively drying Yb2O3 powder and SiO2 powder, weighing Yb2O3 and SiO2 powder according to a molar ratio of 1:2, adding them into a ball mill for wet ball milling to obtain a second mixed slurry, and drying the second mixed slurry, adding it into a high-temperature furnace for solid phase reaction, and finally crushing and sieving in sequence to obtain a second powder; Step S3, respectively drying Yb2O3 and SiO2 powders, weighing Yb2O3 and SiO2 powders according to a molar ratio of 1:1, adding them into a ball mill for wet ball milling to obtain a third mixed slurry, and drying the third mixed slurry, adding it into a high-temperature furnace for solid phase reaction, and finally crushing and sieving in sequence to obtain a third powder; Step S4, respectively taking Dy2O3, Ho2O3, Er2O3, Tm2O3, Lu2O3 and HfO2 powders and drying them, weighing Dy2O3, Ho2O3, Er2O3, Tm2O3, Lu2O3 and HfO2 powders according to a molar ratio of 0.2:0.2:0.2:0.2:0.2:2, adding them into a ball mill for wet ball milling to obtain a fourth mixed slurry, and after drying the fourth mixed slurry, adding it into a high-temperature furnace for solid phase reaction, and finally crushing and sieving them in sequence to obtain a fourth powder; Step S5, adding adhesive and solvent to the first powder, the second powder, the third powder and the fourth powder to prepare a slurry with a solid content of 40-55%, and spray granulating them to obtain Si-HfO2 powder, Yb2Si2O7 powder, Yb2SiO5 powder and (Dy 0.2 Ho 0.2 Er 0.2 Tm 0.2 Lu 0.2 )2Hf2O7 powder; Step S6, preparing SiC f / SiC substrate, sandblasting the substrate surface to an average roughness Ra of 5-8 μm, then ultrasonically cleaning and drying the substrate, and fixing the substrate on a spraying fixture; Step S7, evacuate the plasma spray-physical vapor deposition chamber, then preheat the substrate, and when the substrate is preheated to the set temperature, switch to the spraying program, control the powder feeder to sequentially deliver Si-HfO2 powder, Yb2Si2O7 powder, Yb2SiO5 powder, (Dy 0.2 Ho 0.2 Er 0.2 Tm 0.2 Lu 0.2 )2Hf2O7 powder, and spray the bonding layer Si-HfO2, Yb2Si2O7 intermediate layer, Yb2SiO5 intermediate layer and (Dy 0.2 Ho 0.2 Er 0.2 Tm 0.2 Lu 0.2 )2Hf2O7 top layer, cooled to obtain Si-HfO2 / Yb2Si2O7 / Yb2SiO5 / (Dy 0.2 Ho 0.2 Er 0.2 Tm 0.2 Lu 0.2 )2Hf2O7 thermal / environmental barrier coating.
4. The method for preparing a thermal / environmental barrier coating with high thermal insulation, thermal shock resistance and CMAS corrosion resistance according to claim 3, characterized in that: In step S1, step S2, step S3 and step S4, the powder drying temperature is 100-120°C, and the drying time is 1-3h; the steps of wet ball milling are specifically as follows: Si and HfO2 powders, Yb2O3 powders and SiO2 powders, Dy2O3, Ho2O3, Er2O3, Tm2O3, Lu2O3 and HfO2 powders are respectively added into a ball mill with anhydrous ethanol as a solvent and ball milling beads for wet ball milling, wherein the mass ratio of the added powder, anhydrous ethanol and ball milling beads is 1:0.8:1; the rotation speed of the wet ball milling is 450-550rpm, the mixing time is 10-16h, and the drying temperature of the first mixed slurry, the second mixed slurry, the third mixed slurry and the fourth mixed slurry is 80-100°C, and the drying time is 12-14h.
5. The method for preparing a thermal / environmental barrier coating with high thermal insulation, thermal shock resistance and CMAS corrosion resistance according to claim 1, characterized in that: The temperature of the solid phase reaction in step S2, step S3 and step S4 is 1400-1550°C, the solid phase reaction time is 4-8h, and the median particle size of the second powder, the third powder and the fourth powder is 30-50μm.
6. The method for preparing a thermal / environmental barrier coating with high thermal insulation, thermal shock resistance and CMAS corrosion resistance according to claim 1, characterized in that: In step S5, the amount of adhesive added is 4-8%, the inlet temperature is 200-300° C., the outlet temperature is 90-130° C., the frequency of the atomizing disk is 20-50 Hz, and the speed of the feed pump is 30-50 rpm.
7. The method for preparing a thermal / environmental barrier coating with high thermal insulation, thermal shock resistance and CMAS corrosion resistance according to claim 1, characterized in that: In step S6, the sandblasting pressure is 0.3-0.4 MPa, the sandblasting angle is 50-60°, the sandblasting distance is 120-150 mm, the sandblasting time is 1-3 min, and the solvents for ultrasonic cleaning are kerosene, acetone, and alcohol, respectively.
8. The method for preparing a thermal / environmental barrier coating with high thermal insulation, thermal shock resistance and CMAS corrosion resistance according to claim 1, characterized in that: The vacuuming of the cabin in step S7 is specifically as follows: the cabin pressure is pumped down to 0.5 mbar, and then Ar is backfilled to 40 mbar. After the Ar backfilling is completed, the spray gun is ignited, and the vacuum system is turned on again to pump the cabin pressure down to 1.5 mbar; the current for spraying the bonding layer Si-HfO2 is 1650 A, the flow rate of argon is 110 liters / minute, the flow rate of hydrogen is 6 liters / minute, the powder feeding rate is 8 g / min, the spray distance is 400 mm, the preheating temperature is 500 ° C, and the pressure is 40 mbar; the spraying of Yb2Si2O7 The current of the interlayer is 2600A, the flow rate of argon is 100 liters / minute, the flow rate of helium is 20 liters / minute, the powder feeding rate is 20g / min, the spray distance is 1000mm, the preheating temperature is 900℃, and the pressure is 1.5mbar; the current of the Yb2SiO5 interlayer spraying is 2600A, the flow rate of argon is 100 liters / minute, the flow rate of helium is 20 liters / minute, the powder feeding rate is 20g / min, the spray distance is 1000mm, the preheating temperature is 900℃, and the pressure is 1.5mbar; the spraying (Dy 0.2 Ho 0.2 Er 0.2 Tm 0.2 Lu 0.2 )The current of the top layer of 2Hf2O7 is 2600A, the flow rate of argon is 35 liters / min, the flow rate of helium is 60 liters / min, the powder feeding rate is 20g / min, the spray distance is 1000mm, the preheating temperature is 1000℃, and the pressure is 1.5mbar.
9. Use of the high thermal insulation, thermal shock resistance and CMAS corrosion resistance thermal / environmental barrier coating according to any one of claims 1 to 2 in the preparation of aircraft engine protective coatings.
Citation Information
Cited By
Anti-corrosion and radar-infrared compatible stealth function integrated coating and preparation method thereof
CN121204592A
High-performance composite-structure high-entropy thermal / environmental barrier coating and preparation method thereof
CN122256859A
High performance composite structure high entropy thermal / environmental barrier coating and method of making same
CN122256859B
Integrated coating with water-oxygen corrosion resistance and wave permeability and preparation method thereof
CN122705335A